Application of Dry Colorant Containing Antioxidant from the Waste of Tea Processing for Hypoglicaemic Biscuit Substituted by Suweg (Amorphophallus campanulatus) Flour - Faidah, Nielma Nur; Estiasih, Teti (Fakultas Teknologi Pertanian Universitas Brawijaya, 2009)
The waste of tea extraction has high content of polyphenol. This waste can be processed to be natural brown food colorant that contains antioxidant. Foam mat drying is a suitable method for producing natural brown food colorant. Application of this food dye can be used as colorant agent in hipoglycemic biscuit that does not cause the increase of glucose blood level after consumption. Wheat flour in the making of the biscuit was subtituted by suweg flour. The suweg flour had lower glycaemic index than wheat flour. The combination of natural brown food colorant contained antioxidant and suweg flour subtitution is expected to give functional effect for hypoglycaemic biscuit to prevent the increase of glucose blood level and has antioxidant property.The research comprised of two steps. First step was dry colorant preparation and the second was application of dry colorant for hypoglycaemic biscuit. The randomized block design was employed for each step with two variabels for each. Experiment one: the variables were maltodextrin concentration (6%, 18% b/v) and egg white concentration (1%, 4%, 7% b/v). Experiment two: the variables were dry colorant concentration (2.5%, 5% b/b) and suweg flour-to-wheat flour subtitution level (8%, 24%, 40% b/b). In the second experiment, hypoglycaemic biscuit was tested to wistar rats for determining its effectiveness in reducing blood glucose level compared to control.The result showed that the addition of maltodextrin in dry colorant preparatiom significantly affected antioxidant activity, total phenolic content, color, solubility, and water vapor absorption. The best treatment of dry colorant based on physical and chemical parameters was 18% of maltodextrin concentration and 1% of egg white addition. The characteristics of this dry colorant were as followed: 37.78% of antioxidant activity, 24.12 ppm of total phenolic content, 51.4 of brightness level, 0.074 g/sec of solubility, 8.03% of water vapor absorption. Meanwhile, the addition of egg white significantly affected antioxidant activity, total phenolic content, and color. Subtitution of wheat flour by suweg flour significantly influenced biscuit color and reduced blood glucose level of rats. The best treatment of hypoglycaemic biscuit based on physical, chemical, and bioassay parameters was obtained in 5% dry colorant addition and 10% suweg flour-to-wheat flour substitution level, with characteristics as followed: 35.95% of antioxidant activity, 3.8 ppm of total penolic content, 44.4 of brightness level, 28 mg/dl of blood glucose level reduction.Keywords: the waste of tea extraction, dry colorant containing antioxidant, suweg flour, hipoglycaemic biscuit